Maximum Impact of Ionic Strength on Acid‐Catalyzed Reaction Rates Induced by a Zeolite Microporous Environment. Issue 3 (8th December 2022) - Liu, Qiang; Pfriem, Niklas; Cheng, Guanhua; Baráth, Eszter; Liu, Yue; Lercher, Johannes A.
Abstract: The intracrystalline ionic environment in microporous zeolite can remarkably modify the excess chemical potential of adsorbed reactants and transition states, thereby influencing the catalytic turnover rates. However, a limit of the rate enhancement for aqueous‐phase dehydration of alcohols appears to exist for zeolites with high ionic strength. The origin of such limitation has been hypothesized to be caused by the spatial constraints in the pores via, e.g., size exclusion effects. It is demonstrated here that the increase in turnover rate as well as the formation of a maximum and the rate drop are intrinsic consequences of the increasingly dense ionic environment in zeolite. The molecularly sized confines of zeolite create a unique ionic environment that monotonically favors the formation of alcohol‐hydronium ion complexes in the micropores. The zeolite microporous environment determines the kinetics of catalytic steps and tailors the impact of ionic strength on catalytic rates. Abstract : The confined hydronium ions in zeolite create an intraporous ionic environment, which increases acid‐catalyzed reaction rates in a volcanic pattern at both saturated and low concentrations of substrates in the pores.